Preparation And Characterization Of Iron Oxide Nanocomposite For Removal Of Methylene Blue - Azhari, Azahirah (Universiti Sains Malaysia, 2017)
Iron oxide nanocomposite (Fe2O3-CuO) has been prepared and used as an adsorbent in this study to remove methylene blue. The process to synthesize the samples is based on two methods which are solid state reaction and sol-gel method. Two sample prepared, SS02 (solid state) and SG02 (sol-gel) was further characterized and the micropore surface area and total pore volume is determined. For SS02, the micropore surface area and total pore volume are 5.9476 m2/g and 0.003061 cm3/g respectively. Meanwhile for SG02, the micropore surface area and total pore volume are 11.0242 m2/g and 0.005762 cm3/g respectively. The elemental composition of the samples is obtained by XRD to check the presence of element Fe2O3 and CuO and it shows almost identical pattern for both adsorbent that had been synthesized by different method. The effect of initial dye concentration (25-300mg/L), contact time (0-24 hours) and solution temperature (30-60⁰C) were also evaluated through. However, the adsorption process is not obtained in this study because iron oxide nanocomposite is not suitable for adsorbent in methylene blue removal.